2002
DOI: 10.1038/sj.cdd.4400991
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of eukaryotic apoptosis: the bacterial connection

Abstract: The availability of numerous complete genome sequences of prokaryotes and several eukaryotic genome sequences provides for new insights into the origin of unique functional systemsoftheeukaryotes.Severalkeyenzymesoftheapoptotic machinery, including the paracaspase and metacaspase families of the caspase-like protease superfamily, apoptotic ATPasesand NACHT familyNTPases, and mitochondrial HtrAlike proteases, have diverse homologs in bacteria, but not in archaea.Phylogeneticanalysisstronglysuggestsamitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
342
0
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(350 citation statements)
references
References 79 publications
5
342
0
3
Order By: Relevance
“…We hypothesize that an ancestral cell death mechanism was overlayered with added mechanisms. A popular, plausible 46 yet speculative 47 scenario states that the ancestral cell death mechanism (which may have resembled 'necrosis') might stem from the intrusion of the bacterial precursor of the mitochondrion (the endosymbiont) into the precursor of the eukaryotic cell. In favor of the mitochondrial involvement in the emergence of cell death, it appears that some of the mitochondrial proteins which can be involved in mammalian cell death (such as AIF, cytochrome c, and the serine protease HtrA2/Omi) and in yeast cell death (AIF1) 48 are present in the genome of bacterial ancestors of mitochondria, 46,49 as are the evolutionary ancestors of caspases, the meta-caspases.…”
Section: Hypothetical Evolution Of Cell Death Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesize that an ancestral cell death mechanism was overlayered with added mechanisms. A popular, plausible 46 yet speculative 47 scenario states that the ancestral cell death mechanism (which may have resembled 'necrosis') might stem from the intrusion of the bacterial precursor of the mitochondrion (the endosymbiont) into the precursor of the eukaryotic cell. In favor of the mitochondrial involvement in the emergence of cell death, it appears that some of the mitochondrial proteins which can be involved in mammalian cell death (such as AIF, cytochrome c, and the serine protease HtrA2/Omi) and in yeast cell death (AIF1) 48 are present in the genome of bacterial ancestors of mitochondria, 46,49 as are the evolutionary ancestors of caspases, the meta-caspases.…”
Section: Hypothetical Evolution Of Cell Death Mechanismsmentioning
confidence: 99%
“…A popular, plausible 46 yet speculative 47 scenario states that the ancestral cell death mechanism (which may have resembled 'necrosis') might stem from the intrusion of the bacterial precursor of the mitochondrion (the endosymbiont) into the precursor of the eukaryotic cell. In favor of the mitochondrial involvement in the emergence of cell death, it appears that some of the mitochondrial proteins which can be involved in mammalian cell death (such as AIF, cytochrome c, and the serine protease HtrA2/Omi) and in yeast cell death (AIF1) 48 are present in the genome of bacterial ancestors of mitochondria, 46,49 as are the evolutionary ancestors of caspases, the meta-caspases. 46 As additions to such an ancestral cell death mechanism, while autophagy emerged in evolution before apoptosis and possibly initially only as a restorative pathway, both apoptosis and autophagy might have entered cell death pathways at the dismantling stage, in order to facilitate the disposal of cell corpses ( Figure 3).…”
Section: Hypothetical Evolution Of Cell Death Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct search for the plant orthologs of the core apoptotic cell-death proteins has shown that neither Bcl-2 family members, nor Apaf-1-related proteins or canonical caspases are present in plants. 2,3 Furthermore, numerous cytological observations suggest that plants employ a nonapoptotic pathway of cell dismantling defined as autophagic cell death. 1,4 The hallmark feature distinguishing this type of cell death from apoptosis is that complete cellular degradation takes place inside the dying cell itself without active participation of phagocytes.…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus far, metacaspases have been found in plants, fungi, protists and some groups of bacteria, whereas paracaspases have been identified in animals, slime molds and bacteria. 9,10 These two groups of proteins share the universally conserved HG-spacer-C cysteine/histidine catalytic dyad motif found in caspases 9 (see Figure 1), placing all three groups into a large family of related thiol endopeptidases that also includes the legumains, hemoglobinases and the bacterial proteases clostripain and gingipain R 11,12 Currently, little is known about the functions of the metacaspases or paracaspases, but comparative genomic studies suggest that they may play a role in cell death in many contexts. For example, paracaspases from humans, zebrafish and C. elegans are predicted to contain death domains (DD), a homotypic protein-protein interaction module found in many molecules involved in metazoan apoptosis, 9 and some metacaspase genes in Arabidopsis appear to contain an Nterminal Zn-Pro domain, a motif also found in LSD-1, a protein known to be involved in PCD in plants.…”
Section: Caspases and Their Relatives In Non-metazoansmentioning
confidence: 99%